2021
DOI: 10.1136/archdischild-2020-319509
|View full text |Cite
|
Sign up to set email alerts
|

Time to desaturation in preterm infants undergoing endotracheal intubation

Abstract: BackgroundNeonatal endotracheal intubation is often associated with physiological instability. The Neonatal Resuscitation Program recommends a time-based limit (30 s) for intubation attempts in the delivery room, but there are limited physiological data to support recommendations in the neonatal intensive care unit (NICU). We aimed to determine the time to desaturation after ceasing spontaneous or assisted breathing in preterm infants undergoing elective endotracheal intubation in the NICU.MethodsObservational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In response to this, many strategies have been employed to try and either reduce the need for intubation,21–23 provide greater stability medically during the procedure24 25 or improve education and therefore proficiency of the intubator 26–36. Despite these strategies, intubation remains a problem and by comparison to adult studies our population show high rates of physiological instability and adverse events 5 37–40…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to this, many strategies have been employed to try and either reduce the need for intubation,21–23 provide greater stability medically during the procedure24 25 or improve education and therefore proficiency of the intubator 26–36. Despite these strategies, intubation remains a problem and by comparison to adult studies our population show high rates of physiological instability and adverse events 5 37–40…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal intubation is often associated with repeated attempts and is often associated with physiological instability 4. Hypoxia (as defined by SpO 2 of <90%) has been reported in up to 94% of infants during intubation, particularly those who are preterm 5. The recently completed SHINE trial has shown NHF was associated with increased success rates on first intubation attempt 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional considerations that may account for the rise in hypoxemia include masking hypoxemic bradycardia with atropine, and hypoventilation-induced hypoxemia with paralytic use. 29 , 30 Our protocol attempted to minimize these causes by limiting views to 30 seconds. 29 , 31 Of note, a recent randomized control trial using a high-flow nasal cannula offers a potential intervention to reduce hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 Our protocol attempted to minimize these causes by limiting views to 30 seconds. 29 , 31 Of note, a recent randomized control trial using a high-flow nasal cannula offers a potential intervention to reduce hypoxemia. 32 …”
Section: Discussionmentioning
confidence: 99%